Soft light antifouling ceramic and preparation method thereof
By optimizing the preparation raw materials of ceramic antifouling glaze layer and antifouling materials, combined with sintering treatment and coating technology of antifouling materials, the problems of many ceramic surface defects, lack of wear resistance and unsatisfactory antifouling effect are solved, and the ceramic antifouling effect is achieved. Highly abrasion-resistant, antibacterial and stain-resistant, while maintaining a soft-glossy texture.
Patent Information
- Application Number
- CN202411926639.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The ceramics prepared in the prior art have many defects and are not wear-resistant, and excessive polishing has light pollution, and the wear resistance, antibacteriality and antifouling effect are not ideal.
By optimizing the preparation raw materials of the antifouling glaze layer and the preparation raw materials of the antifouling material, combined with the use of defoaming agents and binders, the probability of bubble generation is reduced, and the density and apparent quality are optimized through the sintering process. The antifouling material consists of nanowax, film-forming agent, nanoindium oxide, nanotitanium dioxide, etc., and is coated through a frictional heat device to fill the pores.
Significantly improves the density and apparent quality of ceramics, enhances wear resistance, antibacterial and antifouling effects, avoids light pollution, and maintains soft light texture.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of building material preparation, and in particular to soft light anti-fouling ceramics and a preparation method thereof. Background Art
[0002] The microstructure of the ceramic surface, such as surface roughness, number, size and shape of defects (bubbles, pinholes, microcracks, etc.), are all factors that affect the antifouling performance. After the ceramic is polished, the pores on the surface will be opened, and microcracks of varying degrees will appear on the surface. When pollutants come into contact with the ceramic surface, due to the capillary action of the surface, part of the pollutants penetrate into the open pores, and the microcracks on the ceramic surface will also adhere to the pollutants, thereby affecting the appearance. In order to form a dense and continuous inorganic ceramic film on the ceramic surface, the existing technology prevents the ceramic surface from being polluted by coating a layer of antifouling agent on the ceramic surface. The antifouling agent is essentially an organic substance with excellent spreadability. The composition of different antifouling agents is different, but the principle is basically the same. Under the action of the capillary force of the pores on the ceramic surface and the external physical and chemical forces, the antifouling agent penetrates into the pores of the brick blank, and the penetration depth can reach 0.5mm~2mm. For example, using silica sol to fill the holes and then polishing it will give it good antifouling properties, but the wear resistance and antibacterial properties need to be improved, and the glossiness after polishing is >90°, which cannot meet the use requirements of soft light. For example, the Chinese patent application number CN110577412A discloses a soft light brick antifouling treatment process, which can improve the antifouling resistance of soft light bricks through polishing, super clean and bright treatment, and nano antifouling treatment, but the antibacterial property needs to be improved. In addition, although antifouling agents can have a certain antifouling effect, they generally have the disadvantage of being easy to volatilize and easily cause environmental pollution. In addition, antifouling agents also have the disadvantage of not being wear-resistant, which will affect the hole filling effect during the processing and polishing process, and excessive polishing before applying the antifouling agent will also cause serious light pollution during the production process.
[0003] In the prior art, the composition and preparation process of the glaze are used to increase the densification of the ceramic surface and thus achieve a certain anti-fouling effect. For example, the Chinese patent application number CN202411347065.3 discloses a method for preparing a super anti-fouling light-sensitive glaze. By optimizing the raw materials, the ceramic has an anti-fouling effect, but there is still room for improvement in wear resistance, antibacterial properties and anti-fouling effects. Summary of the invention
[0004] Based on this, in order to solve the problems that the ceramic surface prepared in the prior art has many defects and is not wear-resistant, excessive polishing causes light pollution, and the wear resistance, antibacterial properties and antifouling effects are not ideal, the present invention provides a soft light antifouling ceramic and a preparation method thereof, and the specific technical scheme is as follows: A soft light anti-fouling ceramic, comprising a ceramic body and a surface glaze layer covering the ceramic body, the surface glaze layer is further covered with an anti-fouling glaze layer, and the anti-fouling glaze layer is infiltrated with an anti-fouling material; The antifouling glaze layer is composed of the following raw materials in parts by weight: 20 to 30 parts of albite, 15 to 25 parts of quartz sand, 25 to 30 parts of calcined kaolin, 5 to 12 parts of antibacterial compound, 1 to 3 parts of strontium titanate, 1 to 2 parts of copper oxide microspheres, 1 to 5 parts of dispersant, 1 to 2 parts of hardener, 1 to 2 parts of binder, 1 to 3 parts of defoamer and 1 to 7 parts of wear-resistant agent; The antibacterial composite is obtained by mixing titanium dioxide, zinc phosphate and tourmaline in a mass ratio of (1-3): (1-7): (1-2); The antifouling material is composed of the following raw materials in parts by weight: 5 to 10 parts of nano wax, 1 to 5 parts of film-forming agent, 1 to 3 parts of nano indium oxide, 1 to 3 parts of nano titanium dioxide, 1 to 3 parts of leveling agent and 1 to 5 parts of silane coupling agent.
[0005] Furthermore, the dispersant is at least one of decaglycerol monostearate, aminopropyltriethoxysilane, organosilicon-modified sodium phosphate and sodium hexametaphosphate.
[0006] Furthermore, the hardener is at least one of tetraethyl orthosilicate and tetramethyl orthosilicate.
[0007] Furthermore, the defoaming agent is polymethylsiloxane.
[0008] Furthermore, the wear-resistant agent is obtained by mixing wollastonite and zirconium oxide in a mass ratio of (1-9):(1-3).
[0009] Furthermore, the film-forming agent is at least one of hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose and sodium carboxymethyl cellulose.
[0010] Furthermore, the leveling agent is at least one of a polyacrylate leveling agent and dodecyl pyrrolidone.
[0011] In addition, the present invention also provides a method for preparing soft light anti-fouling ceramics, the preparation method comprising the following steps: Forming a glaze layer on the surface of the ceramic body by conventional methods; According to the weight ratio, albite, quartz sand, calcined kaolin, antibacterial compound, strontium titanate, copper oxide microspheres, dispersant, hardener, binder, defoamer and wear-resistant agent are uniformly mixed, ball milled, the mixture is sieved through 100-150 meshes, and allowed to stand for aging to obtain an antifouling glaze; Applying the antifouling glaze on the surface glaze layer, drying and sintering to form an antifouling glaze layer; According to the target glossiness, the antifouling glaze layer is polished to obtain a rough soft-light antifouling ceramic; Nano-indium oxide, nano-titanium dioxide and a silane coupling agent are mixed according to weight ratio, and treated at 45°C to 65°C for 20min to 45min, and then nano-wax, a film-forming agent and a leveling agent are added, and stirred at 60°C to 85°C for 1h to 2h to obtain an antifouling material; The antifouling material is coated on the antifouling glaze layer by using a device that can generate friction heat with the polishing surface to fill the holes, and then left to stand for 3d to 5d to obtain soft light antifouling ceramics.
[0012] Furthermore, the amount of the antifouling glaze applied is 520 g / m 2 ~560 g / m 2 .
[0013] Furthermore, the coating amount of the antifouling material is 35g / m 2 ~50g / m 2 .
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention optimizes the raw materials for preparing the antifouling glaze layer, reduces the probability of bubble generation during the preparation process, combines defoaming agents and binders to promote compatibility between components, further reduces bubble generation, and then optimizes the sintering process to reduce the probability of pore generation during the sintering process, thereby making the density and apparent quality of the antifouling glaze layer better; wherein, titanium dioxide, zinc phosphate and tourmaline are compounded for use, tourmaline effectively inhibits the recombination of photogenerated electrons and holes of titanium dioxide, and promotes the red shift of ultraviolet-visible diffuse reflection absorption, exerting an excellent photodegradation effect, and combined with the water resistance and load capacity of zinc phosphate, it can significantly improve the hydrophobic effect of ceramics, thereby having excellent antifouling performance, and strontium titanate, copper oxide microspheres, hardeners and wear-resistant agents are also added to the antifouling glaze, which synergistically resist bacteria while significantly improving the wear resistance of the antifouling glaze layer, reducing the impact of the environment on the antifouling glaze layer, thereby reducing the probability of pollutants accumulating on the ceramic surface, and indirectly achieving an antifouling effect.
[0015] 2. Under the coating pressure, the anti-fouling material of the present application can further fill the tiny holes of the ceramic with nano-scale raw materials, making the microstructure smoother and more uniform. In addition, the anti-fouling material can also form a tight molecular bond structure with the raw materials of the anti-fouling glaze layer, so that the ceramic has better wear resistance and stability in use, and can remain bright and clean after long-term use. Among them, the mixed treatment and modification of nano-indium oxide, nano-titanium dioxide and silane coupling agent can effectively increase their dispersibility and compatibility, and interact with nano-wax and film-forming agent to form a film structure, achieving a certain barrier and anti-fouling effect, and can also achieve the purpose of photocatalytic degradation of organic pollutants.
[0016] 3. Under the interaction of the anti-fouling glaze layer and the anti-fouling material of the present invention, there is no need for excessive polishing, and the ceramic has a soft light texture and is more visually comfortable; and the preparation raw materials of the anti-fouling glaze layer and the anti-fouling material interact with each other to effectively reduce the ability of the ceramic surface to adsorb pollutants, thereby achieving significant wear-resistant, anti-fouling and antibacterial effects as a whole. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.
[0018] One embodiment of the present invention provides a soft light anti-fouling ceramic, the soft light anti-fouling ceramic comprising a ceramic body and a surface glaze layer covering the ceramic body, the surface glaze layer is further covered with an anti-fouling glaze layer, and the anti-fouling glaze layer is infiltrated with an anti-fouling material; The antifouling glaze layer is composed of the following raw materials in parts by weight: 20 to 30 parts of albite, 15 to 25 parts of quartz sand, 25 to 30 parts of calcined kaolin, 5 to 12 parts of antibacterial compound, 1 to 3 parts of strontium titanate, 1 to 2 parts of copper oxide microspheres, 1 to 5 parts of dispersant, 1 to 2 parts of hardener, 1 to 2 parts of binder, 1 to 3 parts of defoamer and 1 to 7 parts of wear-resistant agent; The antibacterial composite is obtained by mixing titanium dioxide, zinc phosphate and tourmaline in a mass ratio of (1-3): (1-7): (1-2); The antifouling material is composed of the following raw materials in parts by weight: 5 to 10 parts of nano wax, 1 to 5 parts of film-forming agent, 1 to 3 parts of nano indium oxide, 1 to 3 parts of nano titanium dioxide, 1 to 3 parts of leveling agent and 1 to 5 parts of silane coupling agent.
[0019] In one embodiment, the copper oxide microspheres have a porous structure, and the nanoparticles also help to increase the surface area, form more electron-hole pairs on the surface, and generate more active sites, which help to improve the photocatalytic degradation effect and antibacterial performance.
[0020] In one embodiment, the dispersant is at least one of decaglycerol monostearate, aminopropyl triethoxysilane, organosilicon-modified sodium phosphate and sodium hexametaphosphate.
[0021] In one embodiment, the hardener is at least one of tetraethyl orthosilicate and tetramethyl orthosilicate.
[0022] In one embodiment, the binder is polyvinyl alcohol.
[0023] In one embodiment, the defoaming agent is polymethylsiloxane.
[0024] In one embodiment, the wear-resistant agent is obtained by mixing wollastonite and zirconium oxide in a mass ratio of (1-9): (1-3).
[0025] In one embodiment, the film-forming agent is at least one of hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose and sodium carboxymethyl cellulose.
[0026] In one embodiment, the leveling agent is at least one of a polyacrylate leveling agent and dodecyl pyrrolidone.
[0027] In addition, the present invention also provides a method for preparing soft light anti-fouling ceramics, the preparation method comprising the following steps: Forming a glaze layer on the surface of the ceramic body by conventional methods; According to the weight ratio, albite, quartz sand, calcined kaolin, antibacterial compound, strontium titanate, copper oxide microspheres, dispersant, hardener, binder, defoamer and wear-resistant agent are uniformly mixed, ball milled, the mixture is sieved through 100-150 meshes, and allowed to stand for aging to obtain an antifouling glaze; Applying the antifouling glaze on the surface glaze layer, drying and sintering to form an antifouling glaze layer; According to the target glossiness, the antifouling glaze layer is polished to obtain a rough soft-light antifouling ceramic; Nano-indium oxide, nano-titanium dioxide and a silane coupling agent are mixed according to weight ratio, and treated at 45°C to 65°C for 20min to 45min, and then nano-wax, a film-forming agent and a leveling agent are added, and stirred at 60°C to 85°C for 1h to 2h to obtain an antifouling material; The antifouling material is coated on the antifouling glaze layer by using a device that can generate friction heat with the polishing surface to fill the holes, and then left to stand for 3d to 5d to obtain soft light antifouling ceramics.
[0028] In one embodiment, the amount of the antifouling glaze applied is 520 g / m 2 ~560 g / m 2 .
[0029] In one embodiment, the ball milling process is performed at a rotation speed of 500 r / min to 1500 r / min and a time of 1 h to 5 h.
[0030] In one embodiment, the static aging time is 12h~24h.
[0031] In one embodiment, the specific gravity of the antifouling glaze is 1.60~2.0.
[0032] In one embodiment, the drying process is carried out at a temperature of 45°C to 70°C.
[0033] In one embodiment, the sintering treatment is: heating to 500°C~800°C at a heating rate of 2°C / min~3°C / min, then heating to 1250°C~1270°C at a heating rate of 15°C / min~20°C / min, keeping warm for 30min~60min, and then cooling to room temperature at a rate of 10°C / min~15°C / min.
[0034] In one embodiment, the target gloss is 20°~60°.
[0035] In one embodiment, the coating amount of the antifouling material is 35g / m 2 ~50g / m 2 .
[0036] In one embodiment, the friction heat is 65°C to 95°C.
[0037] In one embodiment, the coating pressure is 0.8 MPa~1.5 MPa.
[0038] The above scheme can solve the problems of ceramic surface defects and poor wear resistance, excessive polishing causing light pollution, unsatisfactory wear resistance, antibacterial properties and antifouling effects in the prior art by optimizing the raw materials for preparing the antifouling glaze layer and the raw materials for preparing the antifouling material, so as to obtain soft light antifouling ceramics that meet market demand.
[0039] The embodiments of the present invention will be described in detail below with reference to specific examples. Embodiment 1:
[0040] A soft light anti-fouling ceramic comprises a ceramic body and a surface glaze layer covering the ceramic body, the surface glaze layer is further covered with an anti-fouling glaze layer, and the anti-fouling glaze layer is infiltrated with an anti-fouling material; A method for preparing soft light anti-fouling ceramics comprises the following steps: Forming a glaze layer on the surface of the ceramic body by conventional methods; According to the weight ratio, 28 parts of albite, 20 parts of quartz sand, 28 parts of calcined kaolin, 7 parts of antibacterial compound (mixed by titanium dioxide, zinc phosphate and tourmaline in a mass ratio of 3:2:2), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 3 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (mixed by wollastonite and zirconium oxide in a mass ratio of 2:3) are mixed evenly, ball-milled at a speed of 800 r / min for 4 hours, the mixture is sieved through a 100-mesh sieve, and aged for 24 hours to obtain an antifouling glaze with a specific gravity of 1.8; 540g / m 2 The antifouling glaze is applied on the surface glaze layer in an amount of , and dried at 60°C, and sintered. The sintering process is as follows: heating to 500°C at a heating rate of 3°C / min, then heating to 1260°C at a heating rate of 15°C / min, and keeping the temperature for 45 minutes, and then cooling to room temperature at a rate of 10°C / min to form an antifouling glaze layer; According to the target glossiness, the antifouling glaze layer is polished to obtain a rough soft-light antifouling ceramic; According to the weight ratio, 2 parts of nano-indium oxide, 3 parts of nano-titanium dioxide and 5 parts of silane coupling agent were mixed and treated at 60° C. for 30 minutes, and then 9 parts of nano wax, 2 parts of hydroxypropyl cellulose and 1 part of polyacrylate leveling agent were added, and stirred at 65° C. for 1 hour to obtain an antifouling material; The coating was carried out using a device that could generate friction heat of 65°C between the polished surface and the coating pressure of 0.8MPa at 40g / m 2 The antifouling material is coated on the antifouling glaze layer with a coating amount of , and then the antifouling material is filled with holes, and then allowed to stand for 5 days to obtain a soft light antifouling ceramic. Embodiment 2:
[0041] A soft light anti-fouling ceramic comprises a ceramic body and a surface glaze layer covering the ceramic body, the surface glaze layer is further covered with an anti-fouling glaze layer, and the anti-fouling glaze layer is infiltrated with an anti-fouling material; A method for preparing soft light anti-fouling ceramics comprises the following steps: Forming a glaze layer on the surface of the ceramic body by conventional methods; According to the weight ratio, 25 parts of albite, 22 parts of quartz sand, 25 parts of calcined kaolin, 8 parts of antibacterial compound (mixed by titanium dioxide, zinc phosphate and tourmaline in a mass ratio of 3:3:2), 2 parts of strontium titanate, 1 part of copper oxide microspheres, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (mixed by wollastonite and zirconium oxide in a mass ratio of 3:2) are mixed evenly, ball-milled at a speed of 800 r / min for 5 hours, the mixture is passed through a 100-mesh sieve, and aged for 24 hours to obtain an antifouling glaze with a specific gravity of 1.8; 540g / m 2 The antifouling glaze is applied on the surface glaze layer in an amount of , and dried at 65°C, and sintered. The sintering process is as follows: heating to 500°C at a heating rate of 3°C / min, then heating to 1260°C at a heating rate of 15°C / min, and keeping the temperature for 50 minutes, and then cooling to room temperature at a rate of 10°C / min to form an antifouling glaze layer; According to the target glossiness, the antifouling glaze layer is polished to obtain a rough soft-light antifouling ceramic; According to the weight ratio, 2 parts of nano-indium oxide, 3 parts of nano-titanium dioxide and 5 parts of silane coupling agent were mixed and treated at 65°C for 45 minutes, and then 8 parts of nano wax, 2 parts of hydroxypropyl cellulose and 1 part of polyacrylate leveling agent were added, and stirred at 70°C for 1 hour to obtain an antifouling material; The coating was carried out using a device that could generate friction heat of 65°C with the polished surface, with a coating pressure of 1.0 MPa and a pressure of 40 g / m 2 The antifouling material is coated on the antifouling glaze layer with a coating amount of , and then the antifouling material is filled with holes, and then allowed to stand for 5 days to obtain a soft light antifouling ceramic. Embodiment 3:
[0042] A soft light anti-fouling ceramic comprises a ceramic body and a surface glaze layer covering the ceramic body, the surface glaze layer is further covered with an anti-fouling glaze layer, and the anti-fouling glaze layer is infiltrated with an anti-fouling material; A method for preparing soft light anti-fouling ceramics comprises the following steps: Forming a glaze layer on the surface of the ceramic body by conventional methods; According to the weight ratio, 29 parts of albite, 23 parts of quartz sand, 30 parts of calcined kaolin, 7 parts of antibacterial compound (mixed by titanium dioxide, zinc phosphate and tourmaline in a mass ratio of 3:2:2), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (mixed by wollastonite and zirconium oxide in a mass ratio of 3:2) are mixed uniformly, ball-milled at a speed of 800 r / min for 5 hours, the mixture is sieved through a 100-mesh sieve, and aged for 24 hours to obtain an antifouling glaze with a specific gravity of 1.8; 540g / m 2 The antifouling glaze is applied on the surface glaze layer in an amount of , and dried at 70°C, and sintered. The sintering process is as follows: heating to 600°C at a heating rate of 3°C / min, then heating to 1265°C at a heating rate of 15°C / min, and keeping the temperature for 45 minutes, and then cooling to room temperature at a rate of 10°C / min to form an antifouling glaze layer; According to the target glossiness, the antifouling glaze layer is polished to obtain a rough soft-light antifouling ceramic; According to the weight ratio, 3 parts of nano-indium oxide, 2 parts of nano-titanium dioxide and 5 parts of silane coupling agent were mixed and treated at 60°C for 45 minutes, and then 10 parts of nano wax, 2 parts of hydroxypropyl cellulose and 1 part of polyacrylate leveling agent were added, and stirred at 75°C for 1 hour to obtain an antifouling material; The coating was carried out using a device that could generate friction heat of 65°C with the polished surface, with a coating pressure of 1.2Mpa and a pressure of 40g / m 2 The antifouling material is coated on the antifouling glaze layer with a coating amount of , and then the antifouling material is filled with holes, and then allowed to stand for 5 days to obtain a soft light antifouling ceramic.
[0043] Comparative Example 1: The difference between Comparative Example 1 and Example 3 is that the preparation method of the antifouling glaze in Comparative Example 1 is as follows, that is, tourmaline is not added, and the rest is the same as Example 3.
[0044] According to weight ratio, 29 parts of albite, 23 parts of quartz sand, 30 parts of calcined kaolin, 7 parts of antibacterial compound (obtained by mixing titanium dioxide and zinc phosphate in a mass ratio of 5:2), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 2 parts of silicone-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (obtained by mixing wollastonite and zirconium oxide in a mass ratio of 3:2) are mixed evenly, ball milled at a speed of 800 r / min for 5 hours, the mixture is passed through a 100-mesh sieve, and aged for 24 hours to obtain an anti-fouling glaze with a specific gravity of 1.8.
[0045] Comparative Example 2: The difference between Comparative Example 2 and Example 3 is that the preparation method of the antifouling glaze in Comparative Example 2 is as follows, that is, titanium dioxide is not added, and the rest is the same as Example 3.
[0046] According to weight ratio, 29 parts of albite, 23 parts of quartz sand, 30 parts of calcined kaolin, 7 parts of antibacterial compound (obtained by mixing zinc phosphate and tourmaline in a mass ratio of 2:5), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (obtained by mixing wollastonite and zirconium oxide in a mass ratio of 3:2) are mixed evenly, ball milled at a speed of 800 r / min for 5 hours, the mixture is passed through a 100-mesh sieve, and aged for 24 hours to obtain an anti-fouling glaze with a specific gravity of 1.8.
[0047] Comparative Example 3: The difference between Comparative Example 3 and Example 3 is that the preparation method of the antifouling glaze in Comparative Example 3 is as follows, that is, zinc phosphate is not added, and the rest is the same as Example 3.
[0048] According to weight ratio, 29 parts of albite, 23 parts of quartz sand, 30 parts of calcined kaolin, 7 parts of antibacterial compound (obtained by mixing titanium dioxide and tourmaline in a mass ratio of 2:5), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (obtained by mixing wollastonite and zirconium oxide in a mass ratio of 3:2) are mixed evenly, ball milled at a speed of 800 r / min for 5 hours, the mixture is passed through a 100-mesh sieve, and aged for 24 hours to obtain an anti-fouling glaze with a specific gravity of 1.8.
[0049] Comparative Example 4: The difference between Comparative Example 4 and Example 3 is that the preparation method of the antifouling glaze in Comparative Example 4 is as follows, that is, copper oxide microspheres are not added, and the rest is the same as Example 3.
[0050] According to weight ratio, 29 parts of albite, 23 parts of quartz sand, 30 parts of calcined kaolin, 7 parts of antibacterial compound (obtained by mixing titanium dioxide, zinc phosphate and tourmaline in a mass ratio of 3:2:2), 5 parts of strontium titanate, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (obtained by mixing wollastonite and zirconium oxide in a mass ratio of 3:2) are mixed evenly, ball milled at a speed of 800 r / min for 5 hours, the mixture is passed through a 100-mesh sieve, and aged for 24 hours to obtain an anti-fouling glaze with a specific gravity of 1.8.
[0051] Comparative Example 5: The difference between Comparative Example 5 and Example 3 is that the preparation method of the antifouling glaze in Comparative Example 5 is as follows, that is, zirconium oxide is not added, and the rest is the same as Example 3.
[0052] According to the weight ratio, 29 parts of albite, 23 parts of quartz sand, 30 parts of calcined kaolin, 7 parts of antibacterial compound (mixed with titanium dioxide, zinc phosphate and tourmaline in a mass ratio of 3:2:2), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wollastonite were mixed evenly, ball-milled at a speed of 800 r / min for 5 hours, the mixture was sieved through a 100-mesh sieve, and aged for 24 hours to obtain an antifouling glaze with a specific gravity of 1.8 Comparative Example 6: The difference between Comparative Example 6 and Example 3 is that the preparation method of the antifouling glaze in Comparative Example 6 is as follows, that is, no wear-resistant agent is added, and the rest is the same as Example 3.
[0053] According to weight ratio, 29 parts of albite, 23 parts of quartz sand, 30 parts of calcined kaolin, 7 parts of antibacterial compound (obtained by mixing titanium dioxide, zinc phosphate and tourmaline in a mass ratio of 3:2:2), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol and 1 part of polymethylsiloxane are mixed evenly, ball milled at a speed of 800 r / min for 5 h, the mixture is passed through a 100 mesh sieve, and aged for 24 h to obtain an anti-fouling glaze with a specific gravity of 1.8.
[0054] Comparative Example 7: The difference between Comparative Example 7 and Example 3 is that the preparation method of the anti-fouling glaze of Comparative Example 7 is as follows: calcium carbonate raw material is added, and the rest is the same as Example 3.
[0055] According to weight ratio, 27 parts of albite, 23 parts of quartz sand, 20 parts of calcined kaolin, 12 parts of calcium carbonate, 7 parts of antibacterial compound (obtained by mixing titanium dioxide, zinc phosphate and tourmaline in a mass ratio of 3:2:2), 3 parts of strontium titanate, 2 parts of copper oxide microspheres, 2 parts of organosilicon-modified sodium phosphate, 1 part of tetraethyl orthosilicate, 1 part of polyvinyl alcohol, 1 part of polymethylsiloxane and 5 parts of wear-resistant agent (obtained by mixing wollastonite and zirconium oxide in a mass ratio of 3:2) are mixed evenly, ball milled at a speed of 800 r / min for 5 hours, the mixture is passed through a 100-mesh sieve, and aged for 24 hours to obtain an anti-fouling glaze with a specific gravity of 1.8.
[0056] Comparative Example 8: The difference between Comparative Example 8 and Example 3 is that the preparation method of the antifouling material in Comparative Example 8 is as follows, that is, no nano-indium oxide is added, and the rest is the same as Example 3.
[0057] According to the weight ratio, 5 parts of nano titanium dioxide and 5 parts of silane coupling agent were mixed and treated at 60°C for 45 minutes. Then, 10 parts of nano wax, 2 parts of hydroxypropyl cellulose and 1 part of polyacrylate leveling agent were added, and stirred at 75°C for 1 hour to obtain an antifouling material.
[0058] Comparative Example 9: The difference between Comparative Example 9 and Example 3 is that the preparation method of the antifouling material in Comparative Example 9 is as follows, that is, no nano titanium dioxide is added, and the rest is the same as Example 3.
[0059] According to the weight ratio, 5 parts of nano-indium oxide and 5 parts of silane coupling agent were mixed and treated at 60°C for 45 minutes. Then, 10 parts of nano wax, 2 parts of hydroxypropyl cellulose and 1 part of polyacrylate leveling agent were added, and stirred at 75°C for 1 hour to obtain an antifouling material.
[0060] Comparative Example 10: The difference between Comparative Example 10 and Example 3 is that the preparation method of the antifouling material in Comparative Example 10 is as follows, that is, no nano wax is added, and the rest is the same as Example 3.
[0061] According to the weight ratio, 3 parts of nano-indium oxide, 2 parts of nano-titanium dioxide and 5 parts of silane coupling agent were mixed and treated at 60°C for 45 minutes. Then, 2 parts of hydroxypropyl cellulose and 1 part of polyacrylate leveling agent were added, and stirred at 75°C for 1 hour to obtain an antifouling material.
[0062] Comparative Example 11: The difference between Comparative Example 11 and Example 3 is that no antifouling material is added in Comparative Example 11, and the rest is the same as Example 3.
[0063] Comparative Example 12: The sintering treatment in Comparative Example 12 was carried out using conventional techniques, namely, heating to 1260° C. at a heating rate of 20° C. / min and keeping the temperature for 60 min. The rest was the same as in Example 3.
[0064] 1. The hardness and glossiness of the ceramic samples prepared in Examples 1 to 3 were tested. The hardness was tested using a HV-1000 micro-Vickers hardness tester, and the glossiness was measured using an MIT-60 gloss meter at an incident angle of 60°. The results are shown in Table 1 below.
[0065] Table 1: Hardness and glossiness
[0066] From the data analysis of Table 1, it can be seen that the ceramic prepared by the present invention has excellent surface hardness, is strong and wear-resistant, and has a glossiness of 29°~30°, has a soft light texture, and has a decorative effect without light pollution, achieving the purpose of soft light visual comfort.
[0067] 2. The appearance of the antifouling glaze layer after sintering treatment during the preparation of ceramic samples in Examples 1 to 3 and the preparation of ceramic comparative samples in Comparative Examples 1 to 12 was recorded. The results are shown in Table 2 below.
[0068] Table 2: Appearance of antifouling glaze layer
[0069] It can be seen from the sintering treatment results in Table 2 that compared with Example 3, Comparative Examples 1 to 3 are different in the composition of the antibacterial composite, but the appearance of the antifouling glaze layer still has a soft light texture, excellent flatness, no crystallization, bubbles, pinholes, and no cracks, indicating that the antibacterial composite component added by the present invention will not have a significant adverse effect on the appearance of the antifouling glaze layer; in Comparative Example 4, copper oxide microspheres were not added, but the appearance of the antifouling glaze layer was a soft light texture, good flatness, no crystallization, bubbles, and slight pinholes, indicating that the addition of copper oxide microspheres has a positive effect on the appearance quality of the antifouling glaze layer, can play a certain role in promoting diffusion, and reduce the appearance of pinholes in the antifouling glaze layer. Problems; In Comparative Example 5, no zirconium oxide was added, and in Comparative Example 6, no wear-resistant agent was added. The appearance of the antifouling glaze layer was a soft light texture, general flatness, slight crystallization problem, and slight cracking, which shows that adding zirconium oxide in an appropriate amount can promote a more uniform antifouling glaze layer, improve the anti-cracking performance, and thus help to improve the appearance quality of the antifouling glaze layer; In Comparative Example 7, calcium carbonate raw material was added, and the appearance of the antifouling glaze layer was poor in flatness, and obvious bubbles and pinholes appeared, which shows that after the addition of calcium carbonate raw material, the probability of gas appearing in the antifouling glaze layer increased, which significantly affected the appearance quality of the antifouling glaze layer, and the preferred raw materials of the present invention can reduce the occurrence of gas in the sintering process. The probability of gas appearing has a positive impact on the appearance quality of the antifouling glaze layer; in comparative example 8, nano indium oxide is not added, and the appearance of the antifouling glaze layer is slightly crystallized, indicating that the addition of nano indium oxide helps to refine the grains and reduce crystallization, thereby promoting the acquisition of a more excellent appearance quality of the antifouling glaze layer; in comparative example 9, nano titanium dioxide is not added, and the appearance of the antifouling glaze layer is characterized by good flatness, without crystallization, bubbles, or slight pinholes. The addition of nano titanium dioxide in the present invention can improve the melting characteristics of the antifouling material, improve the fluidity of the antifouling material, and promote the acquisition of a smooth, delicate, and pinhole-free antifouling glaze layer; in comparative example 10, nano wax is not added, but the appearance of the antifouling glaze layer appears Slight pinholes indicate that the nano wax can fill the tiny pores in the antifouling glaze layer and increase the apparent quality; in Example 11, no antifouling material was added, but the appearance smoothness of the antifouling glaze layer was average, and obvious pinholes appeared, indicating that the antifouling material can fill the surface pores of the antifouling glaze layer and has a positive effect on the antifouling performance of the ceramic; the sintering treatment in Example 12 adopts conventional technology, but the appearance smoothness of the antifouling glaze layer is average, with slight crystallization and pinhole problems, and cracks, indicating that the firing treatment process is optimized to promote the interaction of the components in the antifouling glaze layer, form a bridging effect, increase the bonding strength of the interface, effectively reduce the occurrence of cracks, and thus obtain a smooth and dense antifouling glaze layer.
[0070] 3. The wear resistance, antifouling and antibacterial properties of the ceramic samples prepared in Examples 1 to 3 and the ceramic comparison samples prepared in Comparative Examples 1 to 12 were tested. The test results are shown in Table 3 below.
[0071] Among them, the wear resistance test is to fix the ceramic samples of Examples 1 to 3 and the ceramic comparison samples of Comparative Examples 1 to 12 on a Minimet 1000 test machine for wear test, the abrasive is emery with 5 mL of water, the rotation speed of the sample is 50 r / min, the wear load is 5N, and the wear rate after 1 hour is tested. The antifouling test is to drip ink on the surface of the corresponding sample to observe whether there are obvious traces; the antibacterial performance refers to JC / T897-2014 (2017).
[0072] Table 3: Abrasion resistance, antifouling and antibacterial properties
[0073] From the data analysis of Table 3, it can be seen that the ceramics prepared by the present invention have significant wear resistance, antifouling and antibacterial properties, and the antibacterial properties change with time, and still have high antibacterial properties, and have long-term antibacterial properties. Specifically, the difference between Comparative Examples 1 to 3 and Example 3 is that the components of the antibacterial composite are different, and they all have high antibacterial properties initially, but as time changes, the antibacterial properties in Comparative Examples 1 to 3 are significantly worse than those in Example 3, indicating that by optimizing the components of the composite antibacterial agent in the present invention, it is helpful to extend the antibacterial properties and promote the antifouling effect. The difference between Comparative Example 4 and Example 3 is that copper oxide microspheres are not added, but the long-term antibacterial properties and wear resistance are worse than those in Example 3, indicating that copper oxide microspheres also play a role in improving wear resistance and antibacterial effects in the antifouling glaze layer, helping to maintain the flatness of the ceramic surface, thereby reducing the probability of dye accumulation on the ceramic surface, and indirectly playing an antifouling effect. Zirconium oxide is not added in Comparative Example 5, and wear-resistant agent is not added in Comparative Example 6. It can be seen that the wear resistance of the ceramic comparison sample is significantly worse than that of Example 3. In Comparative Example 7, calcium carbonate, a raw material that can generate gas, is added, but the antifouling glaze layer formed has problems such as pores, which makes it easy for pollutants to accumulate and also affects the antibacterial performance. Compared with Example 3, Comparative Examples 8 to 9 can be seen that nano-indium oxide and nano-titanium dioxide have a synergistic effect, and the antibacterial performance of a single component is poor. No nano wax is added in Comparative Example 10, but the antifouling performance is worse than that of Example 3, indicating that the nano wax forms an antifouling film on the surface of the antifouling glaze layer, making it difficult for the ceramic to adsorb pollutants and exert significant antifouling performance. No antifouling material is added in Comparative Example 11, and the wear resistance, antifouling and antibacterial properties are significantly worse than those of Example 3, indicating that the antifouling glaze layer of the present application interacts with the antifouling material, which can promote the acquisition of soft light ceramics with better wear resistance, antifouling and antibacterial properties. The sintering process in Comparative Example 12 is different, but as can be seen from Table 2, cracks appeared in the antifouling glaze layer, resulting in failure to obtain better quality ceramics when the antifouling material is subsequently coated, affecting the long-term antibacterial properties of the ceramics, and further affecting the antifouling performance, and failing to meet usage requirements.
[0074] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A soft light anti-fouling ceramic, comprising a ceramic body and a glaze layer covering the ceramic body, characterized in that: The surface glaze layer is also covered with an anti-fouling glaze layer, and the anti-fouling glaze layer is infiltrated with anti-fouling material; The antifouling glaze layer is composed of the following raw materials in parts by weight: 20 to 30 parts of albite, 15 to 25 parts of quartz sand, 25 to 30 parts of calcined kaolin, 5 to 12 parts of antibacterial compound, 1 to 3 parts of strontium titanate, 1 to 2 parts of copper oxide microspheres, 1 to 5 parts of dispersant, 1 to 2 parts of hardener, 1 to 2 parts of binder, 1 to 3 parts of defoamer and 1 to 7 parts of wear-resistant agent; The antibacterial composite is obtained by mixing titanium dioxide, zinc phosphate and tourmaline in a mass ratio of (1-3): (1-7): (1-2); The antifouling material is composed of the following raw materials in parts by weight: 5 to 10 parts of nano wax, 1 to 5 parts of film-forming agent, 1 to 3 parts of nano indium oxide, 1 to 3 parts of nano titanium dioxide, 1 to 3 parts of leveling agent and 1 to 5 parts of silane coupling agent.
2. The soft light anti-fouling ceramic according to claim 1, characterized in that: The dispersant is at least one of decaglycerol monostearate, aminopropyl triethoxysilane, organosilicon-modified sodium phosphate and sodium hexametaphosphate.
3. The soft light anti-fouling ceramic according to claim 1, characterized in that: The hardener is at least one of tetraethyl orthosilicate and tetramethyl orthosilicate.
4. The soft light anti-fouling ceramic according to claim 1, characterized in that: The defoaming agent is polymethylsiloxane.
5. The soft light anti-fouling ceramic according to claim 1, characterized in that: The wear-resistant agent is obtained by mixing wollastonite and zirconium oxide in a mass ratio of (1-9):(1-3).
6. The soft light anti-fouling ceramic according to claim 1, characterized in that: The film-forming agent is at least one of hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose and sodium carboxymethyl cellulose.
7. The soft light anti-fouling ceramic according to claim 1, characterized in that: The leveling agent is at least one of a polyacrylate leveling agent and dodecyl pyrrolidone.
8. A method for preparing soft light antifouling ceramics, characterized in that: The preparation method is used to prepare the soft light anti-fouling ceramic according to any one of claims 1 to 7, and the preparation method comprises the following steps: Forming a glaze layer on the surface of the ceramic body by conventional methods; According to the weight ratio, albite, quartz sand, calcined kaolin, antibacterial compound, strontium titanate, copper oxide microspheres, dispersant, hardener, binder, defoamer and wear-resistant agent are uniformly mixed, ball milled, the mixture is sieved through 100-150 meshes, and allowed to stand for aging to obtain an antifouling glaze; Applying the antifouling glaze on the surface glaze layer, drying and sintering to form an antifouling glaze layer; According to the target glossiness, the antifouling glaze layer is polished to obtain a rough soft-light antifouling ceramic; Nano-indium oxide, nano-titanium dioxide and a silane coupling agent are mixed according to weight ratio, and treated at 45°C to 65°C for 20min to 45min, and then nano-wax, a film-forming agent and a leveling agent are added, and stirred at 60°C to 85°C for 1h to 2h to obtain an antifouling material; The antifouling material is coated on the antifouling glaze layer by using a device that can generate friction heat with the polishing surface to fill the holes, and then left to stand for 3d to 5d to obtain soft light antifouling ceramics.
9. The preparation method according to claim 8, characterized in that: The amount of the antifouling glaze applied is 520g / m 2 ~560g / m 2 .
10. The preparation method according to claim 8, characterized in that: The coating amount of the antifouling material is 35g / m 2 ~50g / m 2 .
Citation Information
Patent Citations
Antifouling treatment technology for soft light tile
CN110577412A
Preparation method of super-antifouling light-sensitive glaze
CN118851803A
Composite antibacterial ceramic glaze and preparation method therefor
CN110790505A
Composite process antibacterial ceramic tile and preparation method thereof
CN113248146A
Ceramic plate nano antifouling preparation, preparation method thereof, antifouling treatment method and soft light antifouling ceramic plate
CN114479534A
Cited By
Jade ceramic tile with soft fat effect and preparation method of jade ceramic tile
CN120607414A